Impact of Welan Gum on Cement Paste Containing PCE Superplasticizers with Different Charge Densities. Issue 5 (5th February 2019) - Wang, Fang; Wang, Dongmin; Wang, Qibao; Yu, Jie; Shi, Jiajia
Abstract: As a renewable materials, welan gum is microbial biopolymer which is fermented by bacteria. It is widely used in self‐compacting concrete because of its excellent rheological properties. After adding welan gum, the fluidity of cement will decrease rapidly. So it needs to be used together with superplasticizer. Two polycarboxylate superplasticizer with the acid/ether radio of 2 (PC‐2)and with the acid/ether radio of 6 (PC‐6)were synthesized. By FTIR measurements, carboxyl functional groups exists in the dialysed polymer. The specific anionic charge density measurement shows that PC‐6 provide more COO − than PC‐2 in alkaline solution. And TOC test analysis shows that the adsorbed amount of PC‐6 is higher than PC‐2 with low anionic charge density. PC‐6 with the higher COO − seems to be more affected by welan gum than PC‐2. From the rheological properties of cement paste mixed with PCEs and welan gum, it can be concluded that the addition of welan gum aggravates the trend of shear thickening. Hydration heat flow at different temperatures indicates the selected welan gum is capable of retarding early cement hydration even in high temperatures. Finally, the film forming property of the welan gum was initially studied through water loss rate test, and the film formation mechanism needs to be studied in the future. Abstract : After adding welan gum, the fluidity of cement will decrease rapidly: Two kinds of polycarboxylate‐based superplasticizer (PCE) with different charge densities (denominated as PC‐2 and PC‐6) were prepared in this study by free radical polymerization. The adsorbed amount of PC‐6 is higher than PC‐2 with low anionic charge density. PC‐6 with the higher COO‐ seems to be more affected by welan gum than PC‐2.